Leaving No One Woman Behind: An Exploration of Gender Equality in Nigeria - Osinaike, Jesudunsin Oluwadara (Curtin University, 2020)
This study explores the gender equality policy framework in Nigeria related to Sustainable Development Goal 5 (SDG5). Using feminist legal theory and grounded theory, it draws on empirical data, interviews and focus groups. The study finds that religio-cultural influences, plural legal system and weak sustainability policy and implementation framework remain drivers of inequality impacting the achievement of SDG5. A nuanced narrative to rethinking the approach to gender equality policy and implementation in Nigeria is provided.